English in Aviation: A Content and Language Integrated Approach - Naumoska, Aneta; Kalajdžisalihović, Nejla (Dobra Knjiga, 2022)
This textbook is primarily intended for upper-intermediate and advanced students of English studying at departments of air traffic, as well as for instructors and researchers interested in English for Specific Purposes (ESP) and contemporary English, whereas a special emphasis has been given to relevant contemporary content and context during the COVID-19 pandemic.